(untitled) (The Strategic Review for Southern Africa, 2024)
Beijing’s influence in Sub-Saharan Africa (SSA) is enduring and expanding, even amid the present decrease in China’s loans to the region. Three interconnected elements contribute to Beijing’s escalating significance: 1) A strategic emphasis on centrality through connectivity integrates African nations into the Beijing sphere, solidifying its pivotal role in the regional production network, extending economic and geopolitical reach, and securing vital resources while building political support; 2) Establishing institutional arrangements that are largely accepted by many African governments enhances Beijing’s appeal as an attractive partner; 3) Power asymmetry positions China as a pervasive actor in the African political economy, wielding tools like debt, financial, and trade dependencies, once exclusive to Western powers (Lendzoumbou 2024). These mechanisms synergistically sustain China’s influence in SSA amid the current cascade of crises.